Induction of anchorage-independent growth of human embryonic fibroblasts with a deletion in the short arm of chromosome 11 by human papillomavirus type 16 DNA. - Smits, H L (1988)
Human embryonic fibroblasts with a large deletion (11p11.11p15.1) in the short arm of one chromosome 11 (del-11 cells) appeared to be susceptible to transformation by early human papillomavirus type 16 (HPV-16) DNA, whereas diploid human embryonic fibroblasts were not. This difference in susceptibility might be explained by the absence of a tumor suppressor gene located within the deleted part on the short arm of chromosome 11. The presence of abundant viral early-gene transcripts in transformed cells suggests that transformation was induced by an elevated level of an HPV-16 early-gene product(s). The low transcriptional activity of HPV-16 in diploid cells may indicate that cellular genes affect viral transcription. Interruption of the HPV-16 E2 early open reading frame is probably required for high-level HPV-16 early-gene expression driven from the homologous enhancer-promoter region.